A review of DC/DC converter-based electrochemical impedance spectroscopy for fuel cell electric vehicles. (October 2019) - Wang, Hanqing; Gaillard, Arnaud; Hissel, Daniel
Abstract: Considering transport applications, there is worldwide an increasing interest in the use of hydrogen-energy for supplying electric powertrains. In order to extend the fuel cell lifespan and to increase its reliability and efficiency, the following features are essential to a fuel cell stack connected DC/DC boost converter: low input current ripple, high voltage gain ratio, high efficiency, high compactness, and high redundancy. Moreover, in order to assess in real time the state-of-health of the fuel cell stack, on-line Electrochemical Impedance Spectroscopy (EIS) functionality integrated with the fuel cell stack connected DC/DC boost converter is a real promising solution requiring no additional measurement equipment. From these points of view, this paper presents a comparison analysis of high voltage gain DC/DC boost converters for fuel cell electric vehicles applications. In addition, some comments and guidelines regarding integration issues are also provided. Highlights: The development status of commercialized FCEVs has been generally studied. Various techniques for FCEV DC/DC converter to gain high performance were compared. Existed diagnostic methods of fuel cell were comparative studied. Requirements of converter-based online fuel cell impedance detection were proposed.